FULFILLMENT OF CONSTITUIONAL RIGHTS OF BELIEFS PARAMASAN UPPER PRIMARY SCHOOL STUDENTS - Raka, Rahmad (JURNAL SOCIUS, 2024)
The existence of believers in various regions in Indonesia should be a concern of the government especially in the field of education after the issuance of Permendikbud No. 27 of 2016 on The Service of Education Penghayat Kepercayaan, no exception the Students of SD Kecil Paramasan Atas as adherents of Kaharingan Trust. This study provides facts that occur in schools and provides answers and solutions on how to learn for Kaharingan Believers students at SD Kecil Paramasan Atas.  This study aims to: (1) Describe the process of religious learning of Kaharingan Believers at SD Kecil Paramasan Atas, (2) Explaining the fulfillment of the rights of kaharingan believers in the learning process at SD Kecil Paramasan Atas, (3) Explaining the impact that occurs unfulfilled rights of Kaharingan Believers in the process of religious learning at SD Kecil Paramasan Atas. This study uses qualitative method, data retrieval technique using purposive sampling.            The results showed that during the process of religious learning students get Islamic subjects, learning is directed to ethics and the planting of good values. Students and parents do not care about the religious lessons taught by the school. The rights of students in education have not been fulfilled, as in the learning process students do not get religious subjects that are in accordance with the beliefs embraced, do not get educators who are in accordance with the beliefs of students. Students have difficulty answering semester exams because the questions obtained are not in accordance with the teaching. The religious value written on the Islamic report card, the value is only a formality because the student does not exist islamic. The problem of believers in SD Kecil Paramasan Atas is complex enough that it needs to be resolved immediately in order for students to get their rights in education.